Innovative Student Projects Combining Traditional Embroidery and 3D Printing in Fashion Design” - Nematova Tursuntosh Alisher qizi (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: This article explores the integration of traditional embroidery with 3D printing in student fashion design projects. Combining heritage embroidery techniques with modern digital fabrication tools allows students to develop creative, technical, and innovative skills. The study examines pedagogical strategies, project implementation, and the benefits of merging traditional craftsmanship with contemporary technology. Research shows that such hybrid projects enhance students’ design competence, problem-solving abilities, and understanding of both cultural heritage and modern innovation.